ASPECTS RELATED TO THE INTERPRETATION OF DISASTER MANAGEMENT AT OPERATIONAL LEVEL - KALAMAR, Norbert; TÖRÖK, Zoltán (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
With the transformation of the disaster management system in Hungary also the alerting system has changed fundamentally. The alerting and deployment nowadays is based totally on informational systems. The deployment of special-purpose trucks in disaster management interventions is often wrongly associated with the words “special” or “extraordinary” by the public, media or even within the disaster management system. In order to clarify the situation, it is important to define the circumstances when special-purpose trucks are deployed in a mission. The authors start with the description of ordinary fire interventions, requiring less forces and resources, and gradually arrives to the interventions with special-purpose trucks, exemplified with case studies. Furthermore, the factors that classify alerts as rescue situations requiring special interventions are also analysed. The paper highlights how the effectiveness of rescue activities can be increased starting with the alert and continued by the intervention. The paper offers insight into the alarm levels and special rescue activities and describes which events demand special-purpose units at the site.